1980
DOI: 10.5014/ajot.34.6.375
|View full text |Cite
|
Sign up to set email alerts
|

Hyper-responsivity to Touch and Vestibular Stimuli as a Predictor of Positive Response to Sensory Integration Procedures by Autistic Children

Abstract: Sensory processing disturbance in autistic children as a predictor of response to sensory integrative procedures was investigated. Ten autistic children, ages 3-1/2 to 13 years (mean, 7.4 years), were initially evaluated in regard to their hypo-, hyper-, or normal responsivity to visual, auditory, tactile, vestibular, proprioceptive, olfactory, and gustatory stimuli. After evaluation, each child received therapy that provided somatosensory and vestibular stimulation and elicited adaptive responses to these sti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
92
0
6

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 191 publications
(101 citation statements)
references
References 6 publications
1
92
0
6
Order By: Relevance
“…We previously presented evidence that administration of VPA on day 12.5 of gestation also has long-term effects on postnatal behaviors in male rats, which include lower sensitivity to pain and higher sensitivity to nonpainful stimuli; diminished acoustic prepulse inhibition; locomotor and repetitive, stereotypic-like hyperactivity combined with lower exploratory activity; decreased number of social behaviors; and increased latency to social behaviors (Schneider et al, 2001;Schneider and Przewlocki, 2005). Similar behavioral abnormalities have been observed in autistic persons (Militerni et al, 2000;Ayres and Tickle, 1980;Allen and Courchesne, 2001;McAlonan et al, 2002;De Moura-Serra, 1990;Pierce and Courchesne, 2001;American Psychiatric Association, 1994). Autistic patients also exhibit enhanced reaction to stress (Tordjman et al, 1997(Tordjman et al, , 1999aMaher et al, 1975;Jansen et al, 2003).…”
Section: Introductionmentioning
confidence: 88%
“…We previously presented evidence that administration of VPA on day 12.5 of gestation also has long-term effects on postnatal behaviors in male rats, which include lower sensitivity to pain and higher sensitivity to nonpainful stimuli; diminished acoustic prepulse inhibition; locomotor and repetitive, stereotypic-like hyperactivity combined with lower exploratory activity; decreased number of social behaviors; and increased latency to social behaviors (Schneider et al, 2001;Schneider and Przewlocki, 2005). Similar behavioral abnormalities have been observed in autistic persons (Militerni et al, 2000;Ayres and Tickle, 1980;Allen and Courchesne, 2001;McAlonan et al, 2002;De Moura-Serra, 1990;Pierce and Courchesne, 2001;American Psychiatric Association, 1994). Autistic patients also exhibit enhanced reaction to stress (Tordjman et al, 1997(Tordjman et al, , 1999aMaher et al, 1975;Jansen et al, 2003).…”
Section: Introductionmentioning
confidence: 88%
“…Sensory integration therapy is often used by occupational therapists to treat children with autism (Ayres & Tickle, 1980). The treatment typically involves vestibular, proprioceptive, auditory, and tactile inputs using brushes, swings, and balls, although other senses may be engaged at the discretion of the therapist.…”
Section: Comparison To Other Autism Treatmentsmentioning
confidence: 99%
“…Ayres showed that tactile defensiveness or overresponsiveness to tactile stimuli was consistently related to hyperactive and distractible behavior in children (Ayres, 1965(Ayres, , 1966(Ayres, , 1969(Ayres, , 1972. Overresponsiveness to tactile stimuli is easily recognized in children (McIntosh, Miller, Shyu, & Dunn, 1999) and there has been some success in treating it with sensory-based interventions (Ayres & Tickle, 1980;Mailloux, 2001;Miller, Wilbarger, Stackhouse, & Trunnell, 2002;.…”
Section: Nih-pa Author Manuscriptmentioning
confidence: 99%
“…NIH-PA Author Manuscript NIH-PA Author Manuscript estimated to occur in 5% of the general population (Ahn, Miller, Milberger, & McIntosh, 2004) and seem to pose a unique challenge for people with developmental disabilities (Baranek, 2002), including autism, attention deficit hyperactivity disorder (ADHD), fragile X syndrome, and other developmental disabilities (Ayres & Tickle, 1980;Baranek, 1999;Baranek & Berkson, 1994;Baranek, Foster, & Berkson, 1997;Cermak & Daunhauer, 1997;Grandin, 1992;Kinnealey, 1973;Larson, 1982;Mangeot et al, 2001;Miller et al, 1999). Understanding the neurobiological processes associated with sensory processing disruptions is important to developing appropriate preventative and intervention approaches.…”
Section: Nih-pa Author Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation